Developing Intercultural Competence in Higher Education: International Students’ Stories And Self-Reflection - Hastowohadi, Hastowohadi; Arief Rusdyansyah; Maria M. Widiantari (Journal of Interdisciplinary Studies in Education, 2024)
In today’s world, despite the abundance of knowledge and connectivity allowed by technologies, there is a growing problem of disconnection among people due to increased polarization and miscommunication. Higher education offers a chance to bridge this gap through the cultivation of intercultural competence. The book by Lily A. Arasaratnam-Smith and Darla K. Deardorff takes a unique approach that combines solid theories with personal stories of international students to make such a concept relatable and actionable. The authors provide practical guidance on enhancing intercultural understanding by emphasizing the need for intentional interventions. Their guidance highlights respect, self-awareness, perspective-taking, listening, adaptability, building relationships, and cultural diversity. It is a valuable resource for educators and students to develop meaningful intercultural competencies.